Comercio electrónico en la empresa Sanfarmedi de la ciudad de Babahoyo periodo 2021. - Guerrero Velásquez, Jonathan Fidel (2022)
This work tries to reflect the importance of the use of the Internet in commercial management. The great technological advances and communication facilities mean that companies carry out various operations every day to exchange information of different kinds. Companies and customers, through time, have been using different means to carry out commercial activity. The incursion of the internet has profoundly marked what companies do and they communicate with each other regardless of the distance that may exist or the place where they are located. The current case study seeks to identify how electronic commerce affects the productive performance that exists in the san farmedi company located in the city of Babahoyo, province of Los Ríos, which is dedicated to the sale of all types of medical, pharmaceutical and, through theoretical bases, I am able to understand the impact that electronic commerce is having on this type of business. Methodological guidelines of a descriptive type with a qualitative approach were established, taking as a population the economically active people of the Babahoyo canton, using relevant techniques and instruments to arrive at the results that derive from inferring about the situation of San Farmedi and thus reach the conclusion that if there is a high level of incidence since san farmi is not having the necessary knowledge for the application of this electronic commerce tool, which indicates poor management in this company.